DETEKSI DINI KANKER LEHER RAHIM MELALUI PEMERIKSAAN IVA TES DI PUSKESMAS PLUPUH I SRAGEN - Wahyuningsih, Istiqomah Risa; Suparmi, S. (P3M STIKES Aisyiyah Surakarta, 2018)
Cervical cancer is one of the cancer that need to watch out for because this cancer occupy the number one cause of death for women in Indonesia. Data from the Health Office Regency of Sragen? in 2017 have 15% positive cases and in 2016 there were 9% positive cases during IVA test. This indicates that the rate of addition of positive IVA test cases is significant. Data obtained from the Plupuh I Public Health Center noted that during 2017, there were 47 positive cases (17%) of the 267 examined. Outcomes in this activity is an increase in the participation of women of childbearing age in early detection of cervical cancer through IVA examination tests and increased knowledge of IVA tests. The IVA examination was carried out at the Plupuh I Public Health Center on February 1, 2018, with a total of 32 participants and all participants participating in IVA tests. From the results of the examination was obtained 5 WUS positive when the examination IVA test and given introduction to conduct further examination at the Public Health Center.